Aesthetics - Valéry, Paul 1871-1945; Manheim, Ralph 1907-; Read, Herbert (London Routledge & Kegan Paul Ltd, 1964)
Essays, lectures, and articles on literature, art and culture.
Includes bibliographical references (pages 281-298) and index.